Carvacrol enhances the antimicrobial potency of berberine in bacillus subtilis - SAYAR, NİHAT ALPAGU; SARIYAR AKBULUT, BERNA (My University, 2022)
The essential oil carvacrol from oregano displays a wide range of biological activities among which is found the inhibition of efflux pumps. Thus, using carvacrol, the current work undertook the effort to potentiate the antimicrobial activity of berberine, a natural product with limited antimicrobial efficacy due to its efflux. Following the selection of concentrations for the combinatorial treatments, guided by checkerboard microtiter plate assay and growth experiments, ethidium bromide accumulation assay was used to find that 25 mu g mL(-1) carvacrol displayed a weak efflux pump inhibitor character in Bacillus subtilis. Scanning electron microscopy images and cellular material leakage assays showed that carvacrol at this concentration neither altered the morphology nor the permeability of the membrane alone but when combined with 75 mu g mL(-1) berberine. Among the efflux pumps of different families found in B. subtilis, except for BmrA and Mdr, the increase in the expressional changes was striking, with Blt displaying similar to 4500-fold increase in expression under the combination treatment. Overall, the findings demonstrated that carvacrol potentiated the effect of berberine; however, not only multiple pumps but also different targets may be responsible for the observed activity.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; Mikrobiyoloji; Yaşam Bilimleri (LIFE); MICROBIOLOGY; Life Sciences (LIFE)